EXPLORING THE MANAGEMENT STRATEGIES OF HEALTH SERVICES AND FACILITIES FOR THE OLDER ADULT IN WEST MANGGARAI, EAST NUSA TENGGARA, INDONESIA - Dewi, Puri Swastika Gusti Krisna; Zaharuddin, Zaharuddin (Jurnal Manajemen Kesehatan Indonesia, 2024)
This study explores the management strategies implemented in health services and facilities for the older adult population in West Manggarai, East Nusa Tenggara, Indonesia. The research focuses on the unique healthcare needs of older adult residents and investigates various approaches adopted by local health institutions to enhance the quality of care, promote accessibility, and address specific challenges associated with aging. The sample for this research consists of 7 health care personnel. The method used in this study was qualitative, involving in-depth interviews. Through an examination of management practices, this study provides valuable insights for the effective strategies of healthcare services for older adult in the region that are faced with limited personnel and facilities.